The Messages on the Use of YouTube Channel as a Self-Disclosure Media for Persons with Disabilities on the Anggi Wahyuda Channel - Nasir, Fuad (Journal of Language, Communication, and Tourism, 2024)
Social media is a means of communication that various people use. Some of them are individuals with disabilities who have been misrepresented in the media and society. The subject of this research is Anggi Wahyuda's YouTube channel, a medium for self-disclosure of its owner. The purpose of this study is to find out messages related to self-disclosure delivered on Anggi Wahyuda's YouTube channel. The method used is a case study. The research then conducted in-depth observations of all aspects of the channel, supported by interviews with the YouTube channel owner and several other relevant informants, including experts from the field of clinical psychology. This study found that the main message to be conveyed was to straighten the general mindset of person with disabilities who were considered miserable.